TELAAH UNSUR BATIN DALAM PUISI BERJUDUL SAJAK IBU KARYA WIJI THUKUL - Pratama, Yosi; Sobari, Teti (IKIP Siliwangi, 2021)
A written work created by someone, is not just a form of expression in expressing his ideas or ideas. But there is a mission or other purpose that he wants to convey to all readers. This study aims to determine the inner elements of poetry in terms of theme, taste, tone and message. The method that the author uses is descriptive qualitative with text as the source of data and the object of the research. Of the many literary works of poetry produced by Indonesian writers, there is one interesting title of poetry to be studied, namely the poem